Penerapan Media Hitung untuk Meningkatkan Hasil Belajar Matematika Pada Siswa Kelas II SDN 2 Dena - Musmulyana, Musmulyana; Khatimah, Husnul; Suciyati, Suciyati (STKIP Taman Siswa Bima, 2024)
The purpose of this study is to determine the improvement in mathematics learning outcomes of second-grade students at SDN 2 Dena through the application of Counting Board Media. This classroom action research was conducted in two cycles, each consisting of planning, action, observation, evaluation, and reflection. The subjects were 26 second-grade students, comprising 16 boys and 10 girls. Data were collected using observation sheets for teaching and learning activities and evaluation tests at the end of each cycle. Success indicators were set at a learning mastery of ≥80% and student learning activities categorized at least as active. The results showed that in Cycle I, the average student score was 84 with a mastery percentage of 78.94%, and student activity was categorized as active with scores of 70 and 75 in the first and second meetings, respectively. In Cycle II, the average score increased to 88.68 with a mastery percentage of 89.47%, and student learning activity reached the very active category with scores of 85 in both meetings. In conclusion, the application of Counting Board Media is effective in improving the mathematics learning outcomes of second-grade students at SDN 2 Dena in the 2023/2024 academic year.